2021
DOI: 10.1140/epjc/s10052-021-09504-y
|View full text |Cite
|
Sign up to set email alerts
|

Thick branes with inner structure in mimetic f(R) gravity

Abstract: In this paper, we study the structure and gravitational resonances of thick branes generated by a mimetic scalar field in f(R) gravity. We obtain several typical thick brane solutions for $$f(R)=R+\alpha R^2$$ f ( R ) = R + α R … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 99 publications
2
17
0
Order By: Relevance
“…Besides that, it has been proved that the original setting of the mimetic theory forecasts that gravitational wave (GW) propagates at the speed of light, confirming agreement with the results of the event GW170817 and its optical counterpart [41,53]. The mimetic gravity is also generalized to the f (R) mimetic gravity [33,38,40,52,[54][55][56][57][58][59][60][61] and the Gauss-Bonnet mimetic gravity [34,[62][63][64]. Especially, a unified formalism of early inflation and late-time acceleration in the frame of the mimetic f (R) gravity was also constructed in [39] where the authors confirmed the inflationary era in contrast to the f (R) gravity.…”
Section: Introductionsupporting
confidence: 67%
“…Besides that, it has been proved that the original setting of the mimetic theory forecasts that gravitational wave (GW) propagates at the speed of light, confirming agreement with the results of the event GW170817 and its optical counterpart [41,53]. The mimetic gravity is also generalized to the f (R) mimetic gravity [33,38,40,52,[54][55][56][57][58][59][60][61] and the Gauss-Bonnet mimetic gravity [34,[62][63][64]. Especially, a unified formalism of early inflation and late-time acceleration in the frame of the mimetic f (R) gravity was also constructed in [39] where the authors confirmed the inflationary era in contrast to the f (R) gravity.…”
Section: Introductionsupporting
confidence: 67%
“…To compute the amplitudes of the diagrams shown in Fig. 1, the effective Lagrangian densities related to the final state are required, which are [31]…”
Section: Theoretical Formalismmentioning
confidence: 99%
“…These findings intrigue an active discussion on the structure of these states. A classical way to describe these states is treating them as candidates of meson-baryon molecular pictur [4,5].…”
Section: Introductionmentioning
confidence: 99%